Increasing the Brand Awareness of Samaya Coffee Shop to Its Target Market Using a Promotional Video - Jabriel Gian Santoso (Kata Kita: Journal of Language, Literature, and Teaching, 2022)
Samaya Coffee Shop is a coffee shop in Solo City. Based on the research that I did, I found that Samaya still lacks of brand awareness, because only a few people know about Samaya. Therefore, the best solution to increase Samaya’s brand awareness is by creating a promotional video with USP (Unique Selling Points). There are several Samaya USPs that I highlight in the video such as the unique menu, private meeting room, and board games. The video is uploaded to Instagram and also to paid promotion accounts in Solo city, so the video could be watched by more target audience. A promotional video is the right effective solution is because video is one of the tools that is often watched by the target market when they seek out and discover the product they want to buy.